STUDENTS’ PERCEPTION AND ATTITUDE ON ‘CODE HUNTING’ FOR OUTDOOR GRAMMAR LEARNING - Huda, Raihan Nashrullah; Sujannah, Wahyu Diny (English Review: Journal of English Education, 2024)
For far too long, grammar lesson has been a concern amongst English teachers and a challenging journey for EFL learners. The conventional grammar learning process tended to be considered boring and complicated by students due to the monotonous teaching method used by teachers which leads to the students’ disengagement. Therefore, the researchers tried to employ a new grammar teaching strategy called ‘Code Hunting’. This survey research aimed to investigate the students’ perspectives towards the use of Code Hunting in the grammar learning process. In this research, the researchers used a quantitative method with descriptive quantitative as the research design. The participants were 60 11th-grade students in one of the senior high schools in Batu, East Java. The findings of this research showed that most students strongly agreed that grammar learning through Code Hunting was easier to understand, far more engaging, and increased their willingness to learn grammar. This research implies that Code Hunting is an effective tool to teach grammar. Thus, it is recommended for English teachers to use Code Hunting and could be offered as a strategy to create an interesting learning experience, especially in the grammar learning process. Furthermore, it is suggested for future researchers to explore more of the students’ perspectives using interview session in order to collect more in-depth information on the impact of Code Hunting.